The Effectiveness of Aerobic Training on Psychological Well-Being of Children with ADHD - Shakib, Zahra; Froumandi, Sahar; Nemati, Sahar; Khodadadi, Neda; Gholamhoseinpour, Hanieh; Akbari, Moslem (Journal of Clinical Physiotherapy Research, 2022)
Introduction: Children with attention-deficit/hyperactivity disorder (ADHD) face many psychological and social problems. This study aimed at investigating the effect of aerobic exercises on the components of psychological well-being of children with ADHD. Materials and Method: For this study, a sample of 30 children diagnosed with ADHD from Qum city was selected by simple convenience sampling and then divided into 2 fifteen-member groups of experimental and control. After that, aerobic exercise training was performed on the experimental group during an eight- week period, three-45 minute session per week. No exercise intervention was applied to the control group. Data analysis was performed using multivariate analysis of covariance via SPSS-22 software. Results: The results of comparing the psychological well-being scores in the post-test compared to the pre-test show a significant increase in the test group after performing aerobic exercises. Conclusion: Aerobic exercise seems to be a suitable treatment strategy without side effects to improve and enhance the psychological well-being of children with ADHD. This finding emphasizes the need for physical activity.